Polarimetric Measurements of Surface Chirality Based on Linear and Nonlinear Light Scattering - Gogoi, Ankur; Konwer, Surajit; Zhuo, Guan-Yu (Frontiers in Chemistry, 2021)
A molecule, molecular aggregate or protein that cannot be superimposed on its mirror image presents chirality. Most living systems are organized by chiral building blocks, such as amino acids, peptides and carbohydrates, and any change in their molecular structure (i.e., handedness or helicity) alters the biochemical and pharmacological functions of the molecules, many of which take place at surfaces. Therefore, studying surface chirogenesis at the nanoscale is fundamentally important and derives various applications. For example, since proteins contain highly ordered secondary structures, the intrinsic chirality can be served as a signature to measure the dynamics of protein adsorption and protein conformational changes at biological surfaces. Furthermore, a better understanding of chiral recognition and separation at bio-nanointerfaces is helpful to standardize chiral drugs and monitor the synthesis of adsorbents with high precision. Thus, exploring the changes in surface chirality with polarized excitations would provide structural and biochemical information of the adsorbed molecules, which has led to the development of label-free and non-invasive measurement tools based on linear and nonlinear optical effects. In this review, the principles and selected applications of linear and nonlinear optical methods for quantifying surface chirality are introduced and compared, aiming to conceptualize new ideas to address critical issues in surface biochemistry.